New Therapeutic Strategies in Small Cell Lung Cancer: The Stem Cell Target - Gallego, Guadalupe Aparicio; Villaamil, Vanessa Medina; Curbera, Guillermo Alonso; Aparicio, L. Antón (IntechOpen, 2012)
None